The Effect of Financial Literacy and Peers towards Saving Behavior with Self-Control as Mediating Variable of Undergraduate Students of Jakarta State University - Setyowati, Endah; Zulaihati, Sri; Fauzi, Achmad (First Ciera Publisher, 2023)
This study aims to find out the effect of financial literacy and peers towards saving behavior with self-control as mediating variable of undergraduate students of Faculty of Economics Jakarta State University. The population in this study were 294 students of the Faculty of Economics, Jakarta State University, class of 2020. In this research, instrument researchers used is quantitative methods, total 170 respondents. Data collection using a questionnaire with accidental sampling. Data is processed using SPSS version 25. The result of this research indicates that 1) Financial literacy has a significant effect on self-control; 2) Peers has a significant effect on self-control; 3) Financial literacy has a significant effect on saving behavior; 4) Peers has a significant effect on saving behavior; 5) Self-control has a significant effect on saving behavior; 6) Financial literacy has an effect on saving behavior with self-control as a mediating variable; 7) Peers has an effect on saving behavior with self-control as a mediating variable.